Greening oil money: the geopolitics of energy finance going green - Koch, Natalie (Energy research & social science, 2022)
This article examines the role of “oil money” in promoting the energy transition, tracing activities across the oil industry and countries heavily dependent on oil revenues to bolster their green credentials. Through a case study of the United Arab Emirates (UAE), I argue that financial sustainability is paramount in places and institutions that feel threatened by fossil fuels divestment efforts and other threats to the oil business and the governmental and financial systems that have been built on and through hydrocarbons. Drawing on research in the UAE from 2014 to 2022, the article illustrates how corporate and government leaders profiting from hydrocarbon sales are searching for diversification opportunities to prolong the benefits of the oil money they control. But given the moral taint of oil money today, these actors are especially interested in the symbolic capital derived from “greening” this oil money by investing in sustainability and energy transition activities - which in turn might even allow them to retain control of global energy systems that they have dominated for so long.